Impact of the Type of Business Activity on The Strategy of Working Capital Management - Mariusz CHUDZICKI (Communications of International Proceedings, 2022)
Most often, the  objectives of an enterprise's activity are defined in two dimensions: short-term (maintaining financial liquidity) and long-term (maximizing market value).  The working capital and  the strategy adopted to a large extent affects the overall financial management of the company.  Adequate working capital management and ensure that the company not only maintains financial liquidity, but also serves to maximize sales, financial results and value of the company.  In the case of investment projects, working capital determines their profitability.  In addition to the presentation of the most important aspects related to working capital, this article  also presents research on the impact of the company's area of activity on working capital.
Keywords: net working capital; financial indicators; the golden rule of balancing; financial liquidity